Using interactive teaching methods in English lessons - N. Karhina (Mukachevo State University, 2023)
Learning foreign languages, in particular English, which is widely spoken internationally, is an important and compulsory part of the educational process in all types of educational institutions. A particularly relevant issue is using modernised teaching tools that can improve the efficiency of the foreign language learning process. The purpose of the study was to identify effective approaches to implementing interactive methods of teaching English. The study uses several methodological tools, namely: analysis, synthesis, comparison, abstraction, and deduction. A survey was conducted among students in grades 2-11 to test the attitude of students to interactive forms of learning and the effectiveness of these new approaches. As a result, it was established that the interactive approach to organising the learning process is the most effective when compared to other methods, as it both accelerates the process of teaching a foreign language, including English and increases its effectiveness. It is proved that interactive teaching methods can be divided into several categories, depending on the actors who implement them and the ways they are used. The study identified that this approach to the learning process ensures the quality development of students' speaking, writing, reading and listening skills. It demonstrates the systematic nature of the interactive approach and the possibility of using it to teach various subjects. The survey identified the level of students' readiness and interest in interactive foreign language learning. The practical value of the research is that it can be used by teachers in preparation for English language classes, and the development of educational plans and programmes at schools.